Pengaruh Online Customer Review dan Online Customer Rating Terhadap Trust dan Keputusan Pembelian Pada Marketplace Shopee - Priyatin, Anteng; Farisi, Herdian (CV ODIS, 2023)
This study aims to examine the impact of online customer reviews, online customer ratings, trust, and purchase decisions on the Shopee online marketplace among Indonesian students. The research employs a quantitative methodology, utilizing a questionnaire as the primary data collection tool. A sample of 200 respondents was selected through purposive sampling. The findings from Structural Equation Modeling (SEM) analysis reveal that online customer reviews exert a significant positive influence on purchase decisions, whereas online customer ratings do not exhibit a significant effect. Both online customer reviews and ratings positively contribute to the establishment of consumer trust. However, the level of trust does not significantly impact purchase decisions. The implications suggest that platforms should enhance their features and services to bolster consumer trust and comprehend the intricate dynamics of how reviews and ratings influence purchase decisions.